2008
DOI: 10.1002/bip.21033
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transdermal delivery of a dipeptide by dermaportation

Abstract: Poor skin permeability and stability limits the application of peptides to the skin. Enhanced skin permeation could offer new therapies for a range of dermatological and cosmetic applications. The aim of this study was to investigate the application of a novel magnetic field enhancement technology to peptide delivery across the skin. Ala-Trp was used as a model dipeptide. Stability of the dipeptide in a range of conditions and with exposure to skin was determined. Dermaportation-magnetic field technology incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Insulin, ketoprofen and vaccines [93,95,165] Increased driving force technologies Iontophoresis Transdermal delivery by a small direct current Charged molecules, peptides, proteins and indomethacin [97,98,166] Dermaportation or magnetophoresis Delivery using static or variable magnetic fields Benzoic acid, terbutaline sulfate, 5-ALA, Ala-Trp (dipeptide) and naltrexone [100][101][102][103][104] ALA: Aminolevulinic acid.…”
Section: Cavitation Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin, ketoprofen and vaccines [93,95,165] Increased driving force technologies Iontophoresis Transdermal delivery by a small direct current Charged molecules, peptides, proteins and indomethacin [97,98,166] Dermaportation or magnetophoresis Delivery using static or variable magnetic fields Benzoic acid, terbutaline sulfate, 5-ALA, Ala-Trp (dipeptide) and naltrexone [100][101][102][103][104] ALA: Aminolevulinic acid.…”
Section: Cavitation Technologiesmentioning
confidence: 99%
“…They suggested that the magnetic fields increased the driving force on the molecules and caused a temporary alteration in skin structure. More recently, work from Australia has found an enhanced penetration of 5-aminolevulinic acid [101], a dipeptide, Ala-Trp [102], and naltrexone [103] through excised human epidermis with application of pulsatile magnetic fields. In addition, the magnetic fields caused enhanced penetration of 10-nm gold nanoparticles into the viable epidermis of excised human full-thickness skin [103].…”
Section: Increased Driving Force Technologiesmentioning
confidence: 99%
“…121,122 Research into dermaportation and other magnetic enhancement techniques is being carried out at Curtin University, Western Australia. Dermaportation has been reported to enhance penetration of 5 -aminolevulinic acid 123 and a dipeptide, Ala -Trp, 124 through human epidermis in vitro . Like Murthy et al, 121,122 Namjoshi et al 124 suggest that the mechanism of enhancement involves both a direct magnetic repulsion on the penetrants and increased permeability due to a rearrangement of the SC lipid bilayers.…”
Section: Increased Driving Force Technologies Dermaportationmentioning
confidence: 99%
“…Dermaportation has been reported to enhance penetration of 5 -aminolevulinic acid 123 and a dipeptide, Ala -Trp, 124 through human epidermis in vitro . Like Murthy et al, 121,122 Namjoshi et al 124 suggest that the mechanism of enhancement involves both a direct magnetic repulsion on the penetrants and increased permeability due to a rearrangement of the SC lipid bilayers. Recent work by Krishnan et al 125 showing that dermaportation caused enhanced naltrexone penetration though human epidermal membranes, but not through silicone membranes, provides some evidence to support a direct effect of pulsed magnetic fi elds on skin.…”
Section: Increased Driving Force Technologies Dermaportationmentioning
confidence: 99%
“…It is believed that the interaction between a pulsed electromagnetic field and the skin could enhance transdermal drug delivery, 20,21 and an electromagnetic field has been shown to induce a change in structures of keratinocytes. 22 Recent developments have also confirmed that the hair follicles play a significant role in transdermal permeation and that the application of massage has a positive effect in follicular penetration.…”
Section: Introductionmentioning
confidence: 99%